2017
DOI: 10.1016/j.ijrefrig.2017.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Review of vapour compression heat pumps for high temperature heating using natural working fluids

Abstract: Highlights Review of recent studies on heat delivery above 80 o C using vapour compression heat pumps  Recent advances in natural fluids as high temperature working fluids  Component development for high temperature heat pump operation  Proposed fluid mixtures, cycle variations, system design in high temperature domain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(53 citation statements)
references
References 93 publications
0
43
0
Order By: Relevance
“…The experimental studies of this type of heat pumps for the production of process heat are limited. Although there are numerous experimental test-rigs for hot water heating mostly for buildings [84][85][86], its industrial application has not been examined so extensively [87]. This has mostly to do with the heat recovery process, requiring lower temperatures as the ones available in most waste heat recovery applications, as previously explained.…”
Section: Transcritical Co 2 Heat Pump Cyclesmentioning
confidence: 99%
“…The experimental studies of this type of heat pumps for the production of process heat are limited. Although there are numerous experimental test-rigs for hot water heating mostly for buildings [84][85][86], its industrial application has not been examined so extensively [87]. This has mostly to do with the heat recovery process, requiring lower temperatures as the ones available in most waste heat recovery applications, as previously explained.…”
Section: Transcritical Co 2 Heat Pump Cyclesmentioning
confidence: 99%
“…In this study, the overall exergy destruction for the vapour compression system is obtained as the accumulation of the exergy destruction in each cycle component, as in Eq. (10).…”
Section: Exergy Analysismentioning
confidence: 99%
“…The working fluid selected for heat pumps determines the maximum performance obtained at certain heat sink temperatures. While at lower temperatures, traditional refrigerants such as HFC-134a, HFC-32, and HC-290 can be used in the industry [9], for high-temperature applications other fluids must be considered [10]. Moreover, for higher heat sink temperatures and temperature lifts, the COP can be improved using advanced configurations, different from the basic cycle [11].…”
Section: Introductionmentioning
confidence: 99%
“…The International Energy Agency (IEA) [5] produced a report on industrial heat pumps, indicating the markets, level of technological maturity, applications and barriers of heat pumps. The report highlights that the theoretical potential for application of industrial heat pumps increases significantly for heat sink temperatures up to and higher than 100 • C. Nellisen and Wolf [6] investigated the heat demand across different industries in the European market and indicated that about 626 PJ (174 TWh) of heat is reachable by industrial heat pumps, of which about 113 PJ (19 %) is in the temperature range 100 • C to 150 • C. Recently, Arpagaus et al [3] presented a comprehensive review on high-temperature heat pump (HTHP) systems, concluding that industrial HTHPs can potentially supply the industrial European demand of 113 PJ.However, the literature highlights that the development of mass-produced units is hindered by many factors, such as low awareness of the heat consumption in companies and the possible technical solutions [3,5]; lack of knowledge of comprehensive heat pump integration methods [3,5,7]; lack of available refrigerants with low global warming potential in the high-temperature range [3,8]; lack of cost-efficient solutions and long payback periods [5,8,9]; and the technical challenges related to the compressor operation at high temperatures [10].…”
Section: Introductionmentioning
confidence: 99%